Sheltering strangers : critical memoirs from hosting Ukrainian refugees - Briggs, Daniel (Bristol University Press, 2025)
This book documents the intimate lives of Ukrainians as they fled their homeland in search of a safe and stable place to stay. The critical memoirs follow the lives of 16 Ukrainian families in a small Spanish town near Madrid and the local families that volunteered to host them during a time of limited state support and an absence of a clear EU plan for the refugees. Through first-hand testimonies, social media messages and photographs, the book reveals the scarring realities of the Ukrainians' upheaval, displacement and trauma alongside the well-meaning sacrifices made by the host families which quickly mutate into moralistic and meritocratic expectations of their new guests. In doing so, the book offers a vivid portrayal of how the tensions of war and displacement play out in real life in real time.
Keywords: Ukrainians -- Spain -- Madrid.; Refugees -- Spain -- Madrid.; Ukrainiens -- Espagne -- Madrid.; Réfugiés -- Espagne -- Madrid.; SOCIAL SCIENCE / Refugees.